Improving Well Productivity through the Combination of Deep Penetrating Perforation and High Energy Gas Fracturing Techniques - Fanata Yudha Nugraha; Brian Tony; Damar Nandiwardhana; Angelica Catharine Zefanya; Nur Ilham Tarsila (Journal of Petroleum and Geothermal Technology, 2023)
Perforation operations often result in formation damage and compacted zones, which can increase skin effect and decrease well productivity. To address these issues, a combination of deep penetrating perforation and high energy gas fracturing techniques can potentially solve these problems. This study utilized commercial software to simulate perforation and fracture geometry, and evaluated productivity using parameters such as skin effect, productivity index, and inflow performance relationships. Results showed that the combination technique increased productivity by 3.34 times compared to conventional perforation and 2.45 times compared to standalone deep penetrating perforation. This suggests that the combination technique effectively improves well productivity by reducing skin effect and increasing productivity index and flow rate. Overall, the study provides promising evidence for the effectiveness of the combination technique in improving well productivity.Keywords:  deep penetrating perforation; geometry; high energy gas fracturing; inflow performance relationship (IPR); productivity index (PI); skin effect